Analysing and Synthesising Morphemes: The Case of Malay Pre-University ESL Students - Engku Haliza, Engku Ibrahim; Azimah, Ahmad Zaki (Publishing Technology, 2017)
The importance of morphological awareness in the development of a learner’s vocabulary size has been well documented. A learner’s ability to analyse and synthesize morphemes at the word level, or coined as morphological awareness, is said to be a significant contributor to his or her vocabulary development. Thus, a learner who has morphological awareness would be able to rely upon their knowledge of a known word to help them derive the meaning of a related though unfamiliar word. Therefore, this study aims to investigate the analytic and synthetic aspects of morphological awareness of 100 Malay pre-university ESL learners. A modified version of the Morphological Awareness Test was used for this purpose.1 Findings of this study revealed that, the students were better able at forming morphologically complex words as compared to their ability to identify morphemes at the word level. The overall results also showed that this group of participants’ morphological awareness level was somewhat low. This study has some practical implications for EFL vocabulary-strategy instruction in the Malaysian setting.